2015
DOI: 10.1371/journal.pone.0132715
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Optimization by Oesophageal Doppler and Pulse Power Wave Analysis in Liver Surgery: A Randomised Controlled Trial

Abstract: Liver surgery is still associated with a high rate of morbidity and mortality. We aimed to compare different haemodynamic treatments in liver surgery. In a prospective, blinded, randomised, controlled pilot trial patients undergoing liver resection were randomised to receive haemodynamic management guided by conventional haemodynamic parameters or by oesophageal Doppler monitor (ODM, CardioQ-ODM) or by pulse power wave analysis (PPA, LiDCOrapid) within a goal-directed algorithm adapted for liver surgery. The p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This is the commonest device used to perform GDFT in the UK, as well as in widespread use internationally 36 , and is the method suggested by NICE in the UK 8 . Evidence has suggested that transoesophageal Doppler and other methods for GDFT such as lithium dilution techniques 37,38 , calibrated pulse contour analysis 39 and the pleth variability index 40 are not interchangeable; hence the decision was taken to make the study population as homogeneous as possible.…”
Section: Discussionmentioning
confidence: 99%
“…This is the commonest device used to perform GDFT in the UK, as well as in widespread use internationally 36 , and is the method suggested by NICE in the UK 8 . Evidence has suggested that transoesophageal Doppler and other methods for GDFT such as lithium dilution techniques 37,38 , calibrated pulse contour analysis 39 and the pleth variability index 40 are not interchangeable; hence the decision was taken to make the study population as homogeneous as possible.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition to standard perioperative monitoring, invasive blood pressure was monitored using the LiDCO plus (LiDCO Ltd, Cambridge, UK). 13 Controlled-goal directed therapy for intravenous fluid administration was applied for the duration of liver resection. 14 After liver resection, goal-directed therapy using fluid challenge and dynamic parameters (stroke volume variation, pulse pressure variation) was applied for patient's volume correction.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of GDFT has been applied to various surgical and intensive care scenarios in the last decade [8][9][10][11]. The aim of the previously published HIPHOP I study was to improve perioperative outcomes of patients undergoing hip revision arthroplasty.…”
Section: Introductionmentioning
confidence: 99%